Emotional discomfort mediates the relationship between self-efficacy and subjective quality of life in people with schizophrenia. (2nd January 2021) - Lee, Stuart J.; Lawrence, Richard; Bryce, Shayden; Ponsford, Jennie; Tan, Eric J.; Rossell, Susan L.
Abstract: Background: In people with schizophrenia, self-efficacy (i.e. the belief in one's capability to perform particular tasks/skills) is associated with and motivates performance of social, health and independent living behaviours. Less well known is whether self-efficacy is associated with subjective quality of life (sQoL) or whether psychopathology impacts this relationship. Aims: Measure whether greater self-efficacy is associated with greater community functioning and sQoL and whether emotional discomfort mediates this relationship. Method: Fifty-two community living people with schizophrenia completed measures of self-efficacy for everyday living and social situations, clinical symptoms, sQoL and community functioning. Results: Greater everyday living and social self-efficacy was significantly correlated with greater sQoL and community functioning and lower emotional discomfort ( p < 0.05). Only social self-efficacy was correlated with negative symptoms. The relationship between both aspects of self-efficacy and sQoL was, however, mediated by emotional discomfort. Greater confidence in performing social and everyday living behaviours therefore indirectly impacted sQoL through reducing emotional distress. Conclusions: Holding negative capability self-beliefs may contribute to poorer outcome for people with schizophrenia. Intervention aimed at facilitating recovery should therefore provide opportunities to develop knowledge and skills required for success in desired life roles and the belief that tasks required for success can be performed.